장피부 누공을 동반한 베체트 장염 환자를 Adalimumab으로 치료한 1예 - 오일환; Il Hwan Oh; 김진옥; Jin Ok Kim; 변영재; Young Jae Byun; 성윤경; Yoon Kyoung Sung; 최찬범; Chan Bum Choi; 김태환; Tae Hwan Kim; et al. (Journal of rheumatic diseases, 2012)
Behcet`s disease (BD) is a multisystemic disorder, which is characterized by recurrent oral aphthous ulcers, genital ulcers, uveitis, and skin lesion. Although intestinal involvement is an uncommon manifestation of the BD, it leads to a poor prognosis, as a result of a high complication, such as intestinal perforation, fistula formation, and massive hemorrhage. Intestinal BD has the tendency for the resistance to conventional medical treatment, and it often requires a surgical intervention because of severe complication. Although the causes of intestinal BD are unknown, some studies show that tumor necrosis factor Alpha (TNF-α) plays a key role in the pathogenesis of BD. Therefore, anti- TNF-α monoclonal antibody, such as adalimumab, is one of the useful treatment for refractory and relapsed intestinal BD. We describe a patient who had intestinal BD complicated enterocutanous fistula with a good response to adalimumab.